Longitudinal analysis of fecal tryptophan metabolites and microbiome composition in very preterm infants: impact of birth mode and feeding type - Naomi V. Wieser; Yannick van Schajik; Mohammed Ghiboub; Nina M. Frerichs; Roni Weiss; Mark Davids; Tim G. J. de Meij; Hendrik J. Niemarkt; Antoine Lefèvre; Patrick Emond; Joep P. M. Derikx; Wouter J. de Jonge; et al. (Gut Microbes)
Preterm birth is associated with increased morbidity and mortality due to factors such as prolonged NICU stays, antibiotic treatments, and immature gastrointestinal and immune systems. These factors disrupt early gut microbial colonization, yet the functional metabolic implications remain understudied. Emerging evidence highlights the role of tryptophan metabolism as a mediator of host–microbiome interactions, critical for intestinal homeostasis and immune regulation. However, its dynamics and relationship with microbial composition in preterm infants are poorly understood. In this study, we longitudinally characterized the microbiome and 21 fecal bioactive tryptophan metabolites during the first month of life in 53 very preterm infants <30 weeks of gestation. Targeted tryptophan metabolomics and 16S rDNA sequencing revealed that cesarean delivery and supplemented feeding was associated with elevated host-derived kynurenine metabolites. Breastfeeding promoted beneficial microbiome colonization, including increased Staphylococcus and reduced Proteobacteria. Notably, Bifidobacterium abundance positively correlated with the AhR ligand indole-3-lactic acid, while Staphylococcaceae negatively associated with indole derivatives. Our findings underscore the link between diet, microbial composition, and tryptophan metabolism in very preterm infants. This work provides a foundation for exploring tryptophan’s role in development, health, and disease, emphasizing the importance of early nutritional strategies.